Effect of cyanide-utilizing bacteria and sulfur on feed utilization, microbiomes, and cyanide degradation in cattle supplemented with fresh cassava root - Napudsawun Sombuddee; Rittikeard Prachumchai; Waroon Khota; Waewaree Boontiam; Anusorn Cherdthong (Scientific Reports, 2023)
Abstract This study aimed to compare the effects of adding cyanide-utilizing bacteria (CUB) and sulfur on rumen fermentation, the degradation efficiency of hydrogen cyanide (HCN), feed utilization, and blood metabolites in beef cattle fed two levels of fresh cassava root (CR). A 2 × 2 factorial arrangement in a 4 × 4 Latin square design was used to distribute four male purebred Thai native beef cattle (2.5–3.0 years old) with an initial body weight (BW) of 235 ± 15.0 kg. Factor A was Enterococcus faecium KKU-BF7 oral direct fed at 108 CFU/ml and 3% dry matter (DM) basis of pure sulfur in concentrate diet. Factor B was the two levels of CR containing HCN at 300 and 600 mg/kg on DM basis. There was no interaction effect between CUB and sulfur supplementation with CR on feed utilization (p > 0.05). Similarly, CUB and sulfur supplementation did not affect (p > 0.05) DM intake and apparent nutrient digestibility. However, the high level of CR supplementation increased (p < 0.05) feed intake and neutral detergent fiber digestibility. The ruminal pH, microbial population, ammonia–nitrogen, blood urea nitrogen, and blood thiocyanate concentrations were unaffected by the addition of CUB and sulfur at two CR concentrations (p > 0.05). The addition of CUB or sulfur had no effect on the efficiency of HCN degradation in the rumen (p > 0.05). However, cattle given CR with HCN at 600 mg/kg DM had considerably higher degradation efficiency than those fed CR containing HCN at 300 mg/kg DM (p < 0.05). The group fed CUB had a considerably greater CUB population (p < 0.05) than the sulfur group. Cyanide-utilizing bacteria or sulfur supplementation with CR had no interaction effect between total VFAs and their profiles (p > 0.05). However, the study observed a significant positive correlation between the amount of CR and the concentration of propionate in the rumen (p < 0.05). The levels of nitrogen absorption and nitrogen retention did not differ significantly among the treatments (p > 0.05). Hence, it may be inferred that the administration of a high concentration of CR at a dosage of 600 mg/kg DM HCN could potentially provide advantageous outcomes when animals are subjected to oral CUB incorporation.